The recourse of annulment of the arbitral award and the right to tantrum - Núñez del Prado Chaves, Fabio (2017)
Is it advisable for a State to eliminate the annulment action of its Law of Arbitration? Can the parties, by virtue of their party autonomy, waive the annulment action?.In the present article, the author demonstrates that the annulment action has a psychological and a legal-political basis, since, on the one hand, it satisfies the psychological need to challenge or contradict, which is inherent of human beings and; on the other, within the framework of Constitutional State it constitutes a democratic tool that guarantees the control of power.